Strengthening Digital Literacy in Cyberbullying Prevention Efforts in Senior Secondary Schools: A Literature Review - Yusuf, Muhammad; Hidayati, Dian; Zuhaery, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
The IT technology development made the purpose of the social media probe very accessible to the target school groups, particularly to high school students. The high usage of social media led to the digitalization of most of the teenagers’ social interaction. The variety in the background and respective digital literacy levels of school students lead to numerous negative effects, including cyberbullying. The aim of the present research is to explore the digital literacy prevention relationship of cyberbullying among high school students through the analysis of the most recent literature survey results. In progresses are utilized the method of system literature review and investigate journals and other scientific articles published between 2020 and 2025. The results of the conducted study showed that good digital literacy, namely, knowledge of digital ethics, helps to regulate students’ thinking and behaving while being on social juvenile media. This in turn can have the benefit of suggesting positive approaches regarding search for the truth and evaluating online content and mitigate the chances to be exposed to cyberbullying. To conclude, based on the results of the conducted study it can be recommended to school administrations to propose a developed digital literacy program, particularly, the one targeting digital ethics to be used as a preventative measure to avoid the negative development of cyberbullying cases in school.